Controversies in the Field of Genocide Studies - Totten, Samuel, author.
1 online resource
Keywords: "At the heart of the field of Genocide Studies lies an active core of vigorous debate that has led to both heated disagreements and productive disputes. This new volume in the Genocide: A Critical Bibliographic Review series focuses on these, as well as other significant issues. Chapters in this volume focus on a number of issues: Did Peru's Aché suffer genocide? What was the role of media propaganda in the Rwandan Genocide, and what more, if anything, could have been done about it? Have Rwanda's post-genocide gacaca courts successfully promoted reconciliation? How has denial affected governmental recognition around the world of the Armenian, Hellenic, and Assyrian genocides? Why have some left-wing 6 rogressives" engaged in denial of the Rwandan Genocide? Has anti-genocide activism had a meaningful effect in prevention of or intervention against genocide?In the pages of this book, readers can explore the various debates that have defined the study of genocide and that are redefining it today. This insightful and provocative volume will entice further discussion on the concept of genocide and will be a must-read for the field of genocide studies."--Provided by publisher.